2006
DOI: 10.1196/annals.1385.002
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Exploitation against Women and Girls with Disability

Abstract: This article seeks to explore issues concerning women and girls with disability who have experienced violence and exploitation. Owing to different methodologies of data collection, it is difficult to precisely determine the exact number of women and girls who are affected. The literature suggests that violence and exploitation against women and girls with disability occur at a rate 50% higher than in the rest of society. It also points out a number of additional critical issues: professionals are uneducated nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Yet there is evidence that a physical disability increases the likelihood of being a victim of crime (for example, Rosen, 2006). One of the few studies examining this issue found that having a physical disability was a significant predictor of fear of crime among young adults in the US (Stiles et al, 2003).…”
Section: Personal Vulnerabilities As Micro-level Predictorsmentioning
confidence: 99%
“…Yet there is evidence that a physical disability increases the likelihood of being a victim of crime (for example, Rosen, 2006). One of the few studies examining this issue found that having a physical disability was a significant predictor of fear of crime among young adults in the US (Stiles et al, 2003).…”
Section: Personal Vulnerabilities As Micro-level Predictorsmentioning
confidence: 99%
“…As noted by Rosen [42], people of African descent are often comfortable using services and strategies that are in line with their belief systems, namely those underpinned by the philosophy of Ubuntu. The services put at the center the elements of reconciliation, restoration and harmony [4], and thus discourage any vengeful behavior by the victim's relatives, prevent future occurrence of the abusive behavior and facilitate the victim's healing.…”
Section: Discussionmentioning
confidence: 96%
“…Rosen (2006) recently reviewed the literature on violence against females with disability and concluded that they experience a 50% greater risk for assault compared to non-disabled men and women. Research also suggests that disabled individuals are at even greater risk if they reside in institutional settings (Sobsey 1994; Jacobson and Richardson 1987).…”
Section: Introductionmentioning
confidence: 99%